Forest diversity promotes individual tree growth in central European forest stands. Issue 1 (17th October 2016) - Chamagne, Juliette; Tanadini, Matteo; Frank, David; Matula, Radim; Paine, C. E. Timothy; Philipson, Christopher D.; Svátek, Martin; Turnbull, Lindsay A.; Volařík, Daniel; Hector, Andy
Summary: Most experimental evidence on the relationship between biodiversity and ecosystem functioning comes from ecosystems with fast‐growing plants, such as grasslands. Although forests provide essential ecological services, they have been less well investigated. We used dendrochronology to compare the tree radial growth rates of four important timber species in replicated, spatially mapped stands that differed in tree composition and diversity within a central European managed forest. Growth rates differed among species but were largely unaffected by the density of neighbouring trees. Increasing stand diversity enhanced individual growth rates, after accounting for the effects of tree density and size. These increases were statistically indistinguishable among the four species. In contrast, the effects of stand and neighbourhood species composition on growth rates were non‐significant. Policy implications . Our study of long‐established central European forest stands revealed levels of tree diversity can be increased in managed forests, with the potential for modest increases in tree growth rates. These results suggest that in addition to the biodiversity and risk mitigation benefits associated with shifting practices away from monoculture management, increased carbon sequestration and yields in mature forests are likely to be realized. Our results suggest that it is possible to increase forest diversity with little or no costs to production and even with the potential for modest increases in tree growth rates.